Leveraging Quizzes and Bamboozles to Engage EFL Students in Online Classes - Syukur Saud; Nur Aeni; Laelah Azizah; Nur Aeni (International Journal of Language Education, 2022)
In creating a comfortable English learning atmosphere,  the impressions of students and lecturers are crucial. Leading the students to be happy in learning is one of the big challenges for the lecturer. The aim of this study is to find out how students and lecturers feel about online learning by using gamification, it investigated how the students engage in the classroom. The mixed approach was used in this study. The information gathered from the questionnaire about students' and lecturers' attitudes toward online learning materials. Using a Likert scale, they were graded. The responses of the students to online learning by applying gamification. The students were enthusiastic and engaged in learning Academic writing by using gamification. The findings of this study are expected to aid teachers and lecturers in gaining insights and prior knowledge when designing the ELT models for an online class. It is also intended to provide feedback on how to enhance the online learning process.